Manganese dioxide nanoflower loaded copper-gallium electrocatalytic synthesis ammonia material prepared based on gallium-based liquid metal
The preparation of manganese dioxide nanoflower supported copper-gallium intermetallic compounds through gallium-based liquid metals solved the problem of catalyst selectivity and low efficiency in electrocatalytic synthesis of ammonia, and achieved efficient and environmentally friendly ammonia synthesis, with the Faraday efficiency reaching 99.36%.
Patent Information
- Application Number
- CN202411526009.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing electrocatalytic ammonia synthesis technology, the selectivity and efficiency of the catalyst are low, and the traditional Haber-Bosch process requires high temperature and high pressure, high resource consumption, and unfriendly environment, and a green alternative is urgently needed.
Manganese dioxide nanoflower-supported copper-gallium intermetallic compounds are prepared using gallium-based liquid metals. The copper ions are anchored in situ through the reduction properties and surface characteristics of liquid metals to form a composite catalytic material for electrocatalytic synthesis of ammonia, improving catalytic activity and Faraday efficiency.
The catalytic activity and Faraday efficiency of copper-based catalytic materials are improved, and efficient ammonia synthesis is achieved. The Faraday efficiency can reach up to 99.36%, and the process is safe and simple to operate, which is suitable for large-throughput preparation.
Smart Images

Figure CN119265604A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic material preparation, and specifically relates to a method for preparing manganese dioxide nanoflower-loaded copper-gallium electrocatalytic ammonia synthesis material based on gallium-based liquid metal. Background Art
[0002] Gallium-based liquid metal, represented by gallium, is an emerging material that is liquid at temperatures close to room temperature. It has both metallic and fluid properties, bringing new opportunities for material design and iteration in many fields. The surface tension of liquid metal is very large. At the same time, because gallium itself has strong reducibility, the surface of liquid metal is a natural preparation and carrier platform for atomic-level two-dimensional materials. This method is simple to prepare and can usually achieve high-throughput preparation. At the same time, the synthesized materials often have a large specific surface area and can provide more active sites, which has great application potential in the field of catalysis.
[0003] Ammonia is an important industrial and agricultural raw material. The main technology for synthesizing ammonia in the world is still the Haber-Bosch process. This method requires a high temperature and high pressure environment during the synthesis process, which will seriously consume resources and is an environmentally unfriendly production method. At present, a greener way of synthesizing ammonia is urgently needed to replace it. Among them, electrocatalytic synthesis of ammonia is a feasible alternative. In the process of electrocatalytic synthesis of ammonia, the selectivity and efficiency of the catalyst are the most critical. Therefore, it is of great significance to study and prepare catalytic materials for efficient electrocatalytic synthesis of ammonia.
[0004] Since manganese plays an important role in enhancing the catalytic activity of nitrogenase, manganese dioxide has been widely studied in the field of nitrogen reduction. Manganese dioxide has a variety of crystal forms and structures, which can provide abundant active sites and have high redox activity. When combined with other materials, it can also form electronic interactions to enhance the activity of the catalyst. Manganese dioxide is abundant in resources and low in cost. Combined with the reducibility of liquid metal, it is easy to form a two-dimensional hierarchical loading substrate.
[0005] Precious metals have natural advantages in the field of catalysis, but they cannot be widely used due to cost issues. In the process of electrocatalytic synthesis of ammonia, copper metal has unique advantages because its electronic structure is similar to that of precious metals, but the ammonia production rate and selectivity of pure copper still need to be further improved. Under certain conditions, gallium metal will react with copper to form intermetallic compounds, thereby changing the electronic configuration of copper metal and affecting its catalytic behavior. In addition, gallium metal is inert to most reactions, and its response overpotential for the largest side reaction of hydrogen evolution in the electrocatalytic synthesis of ammonia is also relatively high, and it has no negative impact on the catalytic system.
[0006] Based on the excellent properties of gallium-based liquid metal, the present invention utilizes its reducibility and surface properties to design and prepare manganese dioxide nanoflowers with a huge specific surface area, and utilizes the negative charge of manganese dioxide in solution to anchor copper ions in situ, and then utilizes the reducibility and wettability of liquid metal to reduce copper and convert it into a copper-gallium intermetallic compound and grow it on the surface of manganese dioxide nanoflowers to form a composite catalytic material. This material is more active than copper materials in electrocatalytic nitrate synthesis of ammonia, and has better selectivity, with a Faraday efficiency of up to 99.36%. Summary of the invention
[0007] The purpose of the present invention is to introduce liquid metal into the field of electrocatalytic ammonia synthesis and improve the ammonia production rate and selectivity of copper-based catalytic materials, and to prepare an electrocatalytic ammonia synthesis material of manganese dioxide nanoflowers loaded with copper-gallium intermetallic compounds. The present invention uses liquid metal as raw material and cleverly utilizes its - and Cu 2+ The reduction properties and wettability of copper are used to control the reduction of manganese dioxide nanoflowers loaded with copper gallium, which is used as a catalyst for the electrocatalytic synthesis of ammonia.
[0008] The present invention innovatively introduces liquid metal into copper-based electrocatalytic ammonia synthesis materials, cleverly utilizing the reducibility of liquid metal twice to design and prepare the material structure, react in situ and do not involve high temperature. The preparation process is safe and easy to operate, and is suitable for large-throughput preparation. This process also successfully improves the catalytic activity and Faraday efficiency of copper-based materials. It provides new ideas and opportunities for expanding the application scenarios of liquid metal and for further improving copper-based electrocatalytic materials, and has certain significance for further research on electrocatalytic ammonia synthesis.
[0009] The present invention uses the surface characteristics and reducibility of gallium-based liquid metal to design the technical scheme of the material. In the process of preparing manganese dioxide nanoflowers, Ga and MnO4 - The potential difference is reduced to MnO2 through the "Galvanic reaction" under acidic conditions. The reaction equation is as follows:
[0010] Ga+MnO4 - +4H + →Ga 3+ +MnO2+2H2O
[0011] The reaction process is limited by the Mott potential, so manganese dioxide can only grow into atomic-level two-dimensional sheets in a self-limiting manner. The sheets are affected by the Maracas force on the surface of the liquid metal, and will separate from the liquid metal surface under slight external disturbance, allowing the reaction to continue. The generated sheets are stacked and folded to eventually form a nanoscale flower-like structure. It is worth noting that during this process, the liquid metal must remain in the liquid phase, otherwise the generated sheets cannot be separated, thus hindering the reaction.
[0012] Since there are many negatively charged O on the surface of manganese dioxide, it can react with Cu 2+ They attract each other through electrostatic interaction, thus completing the anchoring on its surface, and then using the reducibility of liquid metal, Ga and Cu 2+ The potential difference is reduced to the surface of manganese dioxide through the "Galvani reaction". The reaction equation is as follows:
[0013] 2Ga+3Cu 2+ →2Ga 3+ +3Cu
[0014] At the same time, the wettability of Ga on Cu is utilized to further change the reduced copper, and finally the intermetallic compound CuGa2 is generated on the surface of the manganese dioxide nanoflowers.
[0015] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing manganese dioxide nanoflowers loaded with copper gallium electrocatalytic ammonia synthesis material using liquid metal, comprising the following steps:
[0016] Weigh gallium and other low melting point metals and sinter them in a N2 atmosphere at a temperature of 200 to 400°C for 1 to 2 hours to obtain a liquid metal (alloy), wherein the mass ratio of metal gallium is 60% to 90%, the mass ratio of metal indium is 2% to 30%, and the mass ratio of metal tin is 0% to 10%;
[0017] Take 2-15 g of the above liquid metal (alloy), add 0.1-3 mL of 5-45% hydrochloric acid, and then add 5-40 mL of 1×10 -3 ~1×10 -1 M potassium permanganate solution, react in a water bath at 25-90°C for 8-24 hours, and obtain the product (1) after separation.
[0018] The product (1) was added with an excess of 1×10 -3 ~1×10 -1 M potassium permanganate solution, stirred at 25-90°C in a water bath at a speed of 120-200 r / min for 6-24 hours, and dried at 50-90°C after separation to obtain manganese dioxide nanoflowers;
[0019] Take 50-200 mg of the manganese dioxide nanoflowers, add 100-300 mg of copper chloride, add 10-50 mL of DMF solution, and stir magnetically at a speed of 220-400 r / min for 16-32 h to obtain product (2).
[0020] Take 40-120uL of the above liquid metal (alloy), add 10-30mL of DMF solution, and crush it in an ultrasonic cell crusher. The parameters of the ultrasonic crusher are: ultrasound on for 2-5s, off for 2-5s, ultrasonic power set to 40-90%, ultrasonic crushing time for 10-45min, and obtain liquid metal solution (3) after ultrasound;
[0021] The obtained product (2) is added to (3) and ultrasonic crushing is continued. The parameters are set to ultrasonic on for 2 to 5 seconds, off for 2 to 5 seconds, ultrasonic power is set to 45 to 85%, and ultrasonic crushing time is 5 to 45 minutes. After ultrasonication, centrifugal separation is performed, and after drying at 50 to 90° C., a copper gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared using liquid metal (alloy) is obtained.
[0022] The sample performance was evaluated as follows:
[0023] Take 5-20 mg of the prepared sample, add 500-1500 uL of ethanol, then add 20-80 uL of 5% Nafion solution, after water bath ultrasonication for 10-30 min, take 5-30 uL of the solution and drop it onto carbon paper, dry it and wait for testing;
[0024] The test was conducted using an H-type electrolytic cell and a three-electrode system. The two chambers of the electrolytic cell were separated by a proton exchange membrane. The reference electrode used an Ag / AgCl reference electrode, the counter electrode used a platinum electrode, and the electrolyte was 0.1MNO3 - and 0.4MNa2SO4 solution, and adjust the pH value of the test environment as needed. Perform it curve test on the electrochemical workstation for 3600s;
[0025] After the test, the electrolyte in the working electrode chamber was taken and color was developed according to the indophenol blue colorimetric method, and the catalytic rate and Faraday efficiency of the sample were calculated based on the absorbance combined with the standard curve.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] (1) Innovative introduction of liquid metal into the catalytic system;
[0028] (2) Taking advantage of the reducing property of liquid metal, the manganese dioxide precursor is prepared in situ. The galvanic replacement reaction is simpler than conventional hydrothermal synthesis. At the same time, because the growth of manganese dioxide on the surface of liquid metal is limited by the Mott potential, it can only grow self-limitingly into two-dimensional sheets at the atomic level. Under the action of the Maragonni force on the surface of the liquid metal, the sheet and the surface of the liquid metal will separate under external disturbances. The folding and accumulation of the sheet will eventually generate manganese dioxide nanoflowers, which are used as the substrate to anchor the loaded catalyst using its negative charge in the solution;
[0029] (3) Reusing the reducing property of liquid metal to reduce and generate copper on the surface of nanoflowers, and utilizing the wettability of liquid metal to generate copper-gallium intermetallic compound CuGa2 on this basis, and using it as the catalytic main body;
[0030] (4) This catalyst can be applied to a variety of solution systems. - When the concentration is 0.1M, the electrochemical performance is 2.47, 3.25, and 4.75 mg at a potential of -0.5 V vs RHE at pH = 1, 7, and 13, respectively. NH3 / (mg cat h) and the Faradaic efficiencies were 88.03%, 92.61% and 99.36%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the manganese dioxide nanoflowers prepared in Example 3.
[0032] Figure 2 This is a scanning electron microscope image of the catalyst prepared in Example 3.
[0033] Figure 3 This is the XRD pattern of the catalyst prepared in Example 3.
[0034] Figure 4 The performance of the catalyst prepared in Example 3 of the present invention is compared in different pH environments.
[0035] Figure 5 The catalytic performance of the catalyst prepared in Example 3 of the present invention is compared under different potentials under alkaline conditions. DETAILED DESCRIPTION
[0036] Example 1
[0037] The method for preparing a manganese dioxide nanoflower-loaded copper-gallium catalyst of the present invention specifically comprises the following steps:
[0038] Weigh the metal and sinter it in a muffle furnace under N2 atmosphere at 200°C for 1 hour. The resulting alloy is a liquid metal (alloy), in which the mass ratio of gallium is 75%, the mass ratio of indium is 20%, and the mass ratio of tin is 5%.
[0039] Take 10 g of the above liquid metal (alloy), add 0.5 mL of 20% hydrochloric acid, and then add 25 mL of 1×10 -3 M potassium permanganate solution, react in a water bath at 60°C for 16 h, and obtain the product (1) after separation.
[0040] The product (1) was added with an excess of 1×10 -3 M potassium permanganate solution, stirred at 150 r / min in a water bath at 40°C for 16 h, separated and dried at 60°C to obtain manganese dioxide nanoflowers;
[0041] Take 80 mg of the above manganese dioxide nanoflowers, add 160 mg of copper chloride, add 20 mL of DMF solution, and stir magnetically at 400 r / min for 24 h to obtain product (2).
[0042] Take 50uL of the above liquid metal (alloy), add 15mL of DMF solution, and crush it under an ultrasonic cell crusher. The parameters of the ultrasonic crusher are: ultrasound on for 3s, off for 3s, ultrasonic power set to 80%, ultrasonic crushing time for 30min, and obtain liquid metal solution (3) after ultrasound;
[0043] The obtained product (2) was added to (3) and ultrasonic crushing was continued. The parameters were set as ultrasonic on for 3s, off for 3s, ultrasonic power was set to 80%, and ultrasonic crushing time was 15min. After ultrasonication, centrifugal separation was performed, and after drying at 60°C, a copper-gallium electrocatalytic ammonia synthesis material loaded with manganese dioxide nanoflowers prepared using liquid metal was obtained.
[0044] The performance of the sample in 0.1MHNO3+0.4MNa2SO4 electrolyte and -0.5VvsRHE potential is 1.4mg NH3 / (mg cat h), Faraday efficiency is 79.15%
[0045] Example 2
[0046] In the process of preparing manganese dioxide nanoflowers, the reaction liquid metal is kept in a liquid state, otherwise the product cannot be separated from its surface and the reaction process is hindered. In addition, in the subsequent reduction of copper, the liquid metal needs to remain in a liquid state so that it can be ultrasonically broken and the infiltration process after reduction can be carried out. Therefore, in the present invention, we add indium to adjust the melting point of the liquid metal, so as to ensure that the liquid metal is in a liquid state at room temperature and the reaction can proceed smoothly.
[0047] Example 2: Liquid metal with a melting point higher than room temperature is prepared. The solid metal is hindered in the room temperature reaction process. The specific steps are as follows:
[0048] Weigh the metal and sinter it in a muffle furnace under N2 atmosphere at a temperature of 200°C for 1 hour. The resulting alloy is a liquid metal (alloy), in which the mass ratio of metal gallium is 98%, the mass ratio of metal indium is 2%, and the mass ratio of metal tin is 0%.
[0049] Take 8 g of the above liquid metal (alloy), add 0.5 mL of 18% hydrochloric acid, and then add 20 mL of 5×10 -3 M potassium permanganate solution, react in a water bath at 25°C for 24 hours. It was observed that the surface of the liquid metal was dark brown, the solution was still dark purple, and no precipitation was generated at the bottom, indicating that the reaction could not proceed normally.
[0050] We used the manganese dioxide nanoflowers obtained in Example 1 for the subsequent process, taking 100 mg of the above manganese dioxide nanoflowers, adding 200 mg of copper chloride, adding 15 mL of DMF solution, and magnetically stirring at a speed of 300 r / min for 24 h to obtain product (1).
[0051] Take 50uL of the above liquid metal (alloy), add 15mL of DMF solution, and crush it under an ultrasonic cell crusher. The parameters of the ultrasonic crusher are: ultrasound on for 4s, off for 4s, ultrasonic power set to 80%, ultrasonic crushing time for 15min, and obtain liquid metal solution (2) after ultrasound;
[0052] The obtained product (1) was added to (2) and ultrasonic crushing was continued. The parameters were set as ultrasonic on for 4s, off for 4s, ultrasonic power was set to 80%, and ultrasonic crushing time was 15min. After ultrasonication, centrifugal separation was performed, and after drying at 80°C, a copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared using liquid metal was obtained.
[0053] After XRD testing, it was found that the main component of the sample was CuO. Its performance was 1.3 mg in the electrolyte of 0.1 M HNO3 + 0.4 M Na2SO4 at a potential of -0.6 V vs RHE. NH3 / (mg cat h), the Faradaic efficiency is 68.32%.
[0054] Example 3
[0055] The present invention provides a method for preparing a manganese dioxide nanoflower-loaded copper-gallium catalyst, which specifically comprises the following steps:
[0056] Weigh the metal and sinter it in a muffle furnace under N2 atmosphere at a temperature of 200°C for 1 hour. The resulting alloy is a liquid metal (alloy), in which the mass ratio of metal gallium is 75%, the mass ratio of metal indium is 25%, and the mass ratio of metal tin is 0%.
[0057] Take 8 g of the above liquid metal (alloy), add 0.5 mL of 18% hydrochloric acid, and then add 20 mL of 5×10 -3 M potassium permanganate solution, react in a water bath at 80°C for 14 h, and obtain the product (1) after separation.
[0058] The product (1) was added with an excess of 5×10 -3 M potassium permanganate solution, stirred at 80°C in a water bath at a speed of 140 r / min for 14 h, separated and dried at 80°C to obtain manganese dioxide nanoflowers;
[0059] Take 100 mg of the above manganese dioxide nanoflowers, add 200 mg of copper chloride, add 15 mL of DMF solution, and stir magnetically at a speed of 300 r / min for 24 h to obtain product (2).
[0060] Take 50uL of the above liquid metal (alloy), add 15mL of DMF solution, and crush it under an ultrasonic cell crusher. The parameters of the ultrasonic crusher are: ultrasound on for 4s, off for 4s, ultrasonic power set to 80%, ultrasonic crushing time for 15min, and obtain liquid metal solution (3) after ultrasound;
[0061] The obtained product (2) was added to (3) and ultrasonic crushing was continued. The parameters were set as ultrasonic on for 4s, off for 4s, ultrasonic power was set to 80%, and ultrasonic crushing time was 15min. After ultrasonication, centrifugal separation was performed, and after drying at 80°C, a copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared using liquid metal was obtained.
[0062] The basic characterization and performance of Example 3 are shown in the accompanying drawings and their descriptions.
[0063] Figure 1 This is a scanning electron microscope image of the manganese dioxide nanoflower prepared in Example 3. It can be seen that the surface of the sample presents a staggered distribution of nanosheets, which are shaped like flowers and have a sheet thickness of about 10 nm. Figure 2 This is a scanning electron microscope image of the sample prepared in Example 3. It can be seen that spherical substances with a size of about 50 nm have grown from the nanosheet layer of the nanoflower. Figure 3 This is the XRD spectrum of the sample prepared in Example 3. It can be seen from the figure that the sample surface is mainly CuGa2, in addition to which there is also In single substance.
[0064] The sample obtained in Example 3 was tested under the same overpotential conditions, namely, 0.1M HNO3+0.4MNa2SO4 electrolyte; neutral conditions, namely, 0.1MNaNO3+0.4MNa2SO4 electrolyte; and alkaline conditions, namely, 0.1M NaOH+0.4MNa2SO4 electrolyte. The ammonia production rate and Faraday efficiency were shown in Figure 2. Figure 4 As shown, the ammonia production rate and Faraday efficiency of the sample under acidic, neutral and alkaline conditions are 2.47, 3.25 and 4.75 mg respectively. NH3 / (mg cat h) and 88.03, 92.61, 99.36%.
[0065] The sample obtained in Example 3 was tested under the same alkaline conditions at different potentials, namely -0.1, -0.3, -0.5, -0.7, and -0.9 V vs RHE, and the ammonia production rate and Faraday efficiency were 0.59, 2.36, 4.75, 6.41, and 8.41 mg NH3 / (mg cat h) and 95.36, 81.96, 99.36, 84.62, 45.23%, such as Figure 5 shown.
[0066] In summary, although the increase in potential can increase the rate of ammonia production, the side reactions caused by high potential cause the Faraday efficiency to drop significantly. Therefore, the best test environment for the sample is an alkaline environment, and the best test potential is -0.5Vvs RHE, corresponding to an ammonia production rate of 4.75mg NH3 / (mg cat h), the Faraday efficiency can reach 99.36%.
Claims
1. A copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared from gallium-based liquid metal, characterized in that: The negative charge of manganese dioxide in aqueous solution was used to anchor copper ions, and the reducing property of liquid metal was used for in-situ reduction twice to prepare a copper-gallium electrocatalytic ammonia synthesis composite catalyst material loaded on the surface of manganese dioxide nanoflowers.
2. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 1, characterized in that: The manganese dioxide nanoflower is generated by a replacement reaction in an acidic environment using the potential difference between gallium and permanganate ions. The reaction process is restricted by the Mott potential and self-limitedly grows into atomic-level two-dimensional manganese dioxide sheets. After stacking and folding, a nanoscale flower-like structure is finally formed, in which the sheet thickness is 2 to 20 nm.
3. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 1, characterized in that: Cu in solution 2+ There are negatively charged oxygen anions (O - , O 2- 、O2 - Or other negative ion groups) are anchored on the surface of manganese dioxide sheets under the action of electrostatics, and then the reducing property of liquid metal is used, namely Ga and Cu 2+ The potential difference is large, and it is reduced in situ on the surface of manganese dioxide through a replacement reaction to form a copper gallium catalyst.
4. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 3, characterized in that: The main component of the copper-gallium catalyst generated on the surface of manganese dioxide is a copper-gallium intermetallic compound, and its physical phase is mainly CuGa2, in which the valence state of the gallium element is 0 and positive (+1 and +3) coexist, and the valence state of the copper element is 0 and +2 coexist.
5. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 3, characterized in that: The copper-gallium catalyst formed on the surface of manganese dioxide also includes a copper-gallium alloy, in which copper and gallium are both zero-valent elements.
6. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 3, characterized in that: The copper gallium catalyst formed on the surface of manganese dioxide also contains a small amount of the metallic element indium.
7. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal as claimed in claim 3, characterized in that: The copper gallium catalyst formed on the surface of manganese dioxide is spherical in shape with a diameter of 20 to 80 nm.
8. A method for preparing a copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal according to claims 1 to 7, characterized in that: The following steps are involved: Step 1: Preparation of liquid metal: Weigh a low melting point metal and sinter it in a muffle furnace under a N2 atmosphere at a temperature of 200 to 400°C for 1 to 2 hours; the resulting alloy is a liquid metal (alloy), wherein the mass ratio of metal gallium is 60% to 90%, the mass ratio of metal indium is 2% to 30%, and the mass ratio of metal tin is 0% to 10%; Step 2: Preparation of manganese dioxide nanoflowers: Take 2-15 g of the above liquid metal, add 0.1-3 mL of 5-45% hydrochloric acid, and then add 5-40 mL of 1×10 -3 ~1×10 -1 M potassium permanganate solution, react in a water bath at 25-90°C for 8-24 hours, and obtain the product (1) after separation; Then the product (1) was added with an excess of 1×10 -3 ~1×10 -1 M potassium permanganate solution, stirred at 25-90°C in a water bath at a speed of 120-200 r / min for 6-24 hours, and dried at 50-90°C after separation to obtain manganese dioxide nanoflowers; Step 3: Preparation of copper-gallium catalyst supported by manganese dioxide nanoflowers: Take 50-200 mg of the above manganese dioxide nanoflowers, add 100-300 mg of copper chloride, add 10-50 mL of DMF solution, and stir magnetically at a speed of 220-400 r / min for 16-32 h to obtain product (2). Take 40 to 120 uL of the above liquid metal, add 10 to 30 mL of DMF solution, and crush it in an ultrasonic cell crusher; the parameters of the ultrasonic crusher are: ultrasound on for 2 to 5 seconds, off for 2 to 5 seconds, the ultrasonic power is set to 40 to 90%, the ultrasonic crushing time is 10 to 45 minutes, and a liquid metal solution (3) is obtained after ultrasound; The obtained product (2) is added to (3) and ultrasonic crushing is continued; the parameters are set to turn on the ultrasound for 2 to 5 seconds and turn off for 2 to 5 seconds, the ultrasonic power is set to 45 to 85%, and the ultrasonic crushing time is 5 to 45 minutes; after ultrasonication, centrifugal separation is performed, and after drying at 50 to 90° C., a copper gallium electrocatalytic ammonia synthesis material supported by manganese dioxide based on gallium-based liquid metal is obtained.
9. The copper-gallium electrocatalytic ammonia synthesis material supported by manganese dioxide nanoflowers prepared based on gallium-based liquid metal according to claims 1 to 7, characterized in that: When used as a material for electrocatalytic nitrate synthesis of ammonia, at -0.1~-1Vvs RHE, C(NO3 - )=0.1M, under the test environment pH=1, 7, 13, the ammonia production rate is 0.5~8.5mg NH3 / (mg cat ·h), the Faraday efficiency is 40-99.5%; under the conditions of -0.5Vvs RHE and pH=13, the ammonia production rate is 4.75mg NH3 / (mg cat h), the Faraday efficiency can reach 99.36%.
Citation Information
Cited By
Copper-gallium bimetallic silicon-based carrier catalyst and preparation method and application thereof
CN121892149A
A copper-gallium bimetallic silicon-based carrier catalyst, a preparation method and application thereof
CN121892149B
Layered manganese dioxide coated gold nanoparticle photocatalyst and preparation method thereof
CN122076435A